Utilisation of Empty Fruit Bunch and Oil Palm Frond for Volvariella volvacea cultivation and application of spent mushroom substrates in maize production-a review - Abu Bakar, Muhammad Wasil; Uddin, Kamal; Zaibon, Syaharudin; Roslim, Muhammad Huzaifah; Umor, Noor Azrimi; M. Solaiman, Md Zakaria; Haque, Ahmad Numery Ashfa Qul; Khalid, Ariful Islam; Alam, Jahangir (Sciendo, 2024)
Asian countries such as Malaysia and Indonesia are beginning to commercialise the cultivation of Volvariella volvacea as the demand rises. However, production is still low due to a lack of knowledge about formulation and poor handling of the spent mushroom substrates. In Malaysia, this shortage can be addressed by selecting high-yielding biomass such as oil palm biomass that can promote the development of Volvariella. In addition, the substrates from mushroom cultivation can be used as a soil conditioner for crop cultivation. The growth of mushrooms requires enough nutrients and moisture content. Empty fruit bunches (EFB) and oil palm fronds (OPF) are suitable for this purpose as they possess these properties. The use of oil palm biomass as a substrate would increase the mycelium rate, number of needles and weight in a shorter time. On the other hand, the spent mushroom substrates should be a useful material for the cultivation of maize (Zea mays L.) and would improve plant development by increasing soil pH. The importance of EFB and OPF for increasing mushroom yield, and the application of spent substrates in maize cultivation has not yet been established in various studies. This review summarises the properties of oil palm biomass on mushroom development and the application of spent substrates to achieve high maize yields and improve soil physicochemical properties. Future studies should support the utilisation of oil palm biomass for Volvariella cultivation and the use of spent substrates for sustainable maize production.